1999
DOI: 10.1074/jbc.274.49.34773
|View full text |Cite
|
Sign up to set email alerts
|

Differential Temperature-dependent Chaperone-like Activity of αA- and αB-crystallin Homoaggregates

Abstract: ␣-Crystallin, a heteromultimeric protein made up of ␣A-and ␣B-crystallins, functions as a molecular chaperone in preventing the aggregation of proteins. We have shown earlier that structural perturbation of ␣-crystallin can enhance its chaperone-like activity severalfold. The two subunits of ␣-crystallin have extensive sequence homology and individually display chaperonelike activity. We have investigated the chaperone-like activity of ␣A-and ␣B-crystallin homoaggregates against thermal and nonthermal modes of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
97
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(106 citation statements)
references
References 44 publications
9
97
0
Order By: Relevance
“…In order to probe the molecular mechanism of the chaperone-like activity and its enhancement upon structural perturbation, we have been studying ␣-crystallin and its constituent subunits. Our recent study on the ␣A and ␣B homoaggregates showed that, despite high sequence homology, these proteins differ in their stability, chaperone-like activity, and the temperature dependence of this activity (8). This study also indicated different roles for the two proteins in the ␣-crystallin heteroaggregate in the eye lens and as separate proteins in non-lenticular tissues.…”
mentioning
confidence: 81%
“…In order to probe the molecular mechanism of the chaperone-like activity and its enhancement upon structural perturbation, we have been studying ␣-crystallin and its constituent subunits. Our recent study on the ␣A and ␣B homoaggregates showed that, despite high sequence homology, these proteins differ in their stability, chaperone-like activity, and the temperature dependence of this activity (8). This study also indicated different roles for the two proteins in the ␣-crystallin heteroaggregate in the eye lens and as separate proteins in non-lenticular tissues.…”
mentioning
confidence: 81%
“…This difference is not caused by their mode of purification, as demonstrated with His-Hsp22 purified under native conditions and with urea. Small Hsps of other organisms have also been reported to show differences in their chaperone activity; among others, this is the case for Xenopus laevis Hsp30C and Hsp30D (Abdulle et al 2002), for mammalian ␣A-crystallin and ␣B-crystallin (Datta and Rao 1999;Van Boekel et al 1999;Reddy et al 2000) and recently for mammalian Hsp22 (Chowdary et al 2004) and S. cerevisiae Hsp42 and Hsp26 (Haslbeck et al 2004). For example, despite the high degree of sequence homology and structural similarity of ␣A-and ␣B-crystallin, ␣A-crystallin is more efficient in preventing thermal aggregation of proteins whereas ␣B-crystallin performs better against reduction-induced aggregation of proteins (Datta and Rao 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Advances in this direction have centered on the lenticular ␣-crystallins. Recombinant ␣B-crystallin was shown to be a better chaperone than ␣A-crystallin, in particular at physiological temperatures (57,311). Optimal chaperone activity probably is sacrificed for stability reasons in the naturally occurring 3:1 stoichiometry of ␣A-and ␣B-crystallins.…”
Section: Hetero-oligomeric Complexesmentioning
confidence: 99%